2021
DOI: 10.1111/ijn.12933
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motor imagery training on lower limb motor function of patients with chronic stroke: A pilot single‐blind randomized controlled trial

Abstract: Aims This pilot study aimed to evaluate the effects of motor imagery training on lower limb motor function of stroke patients. Background Motor imagery training has played an important role in rehabilitation outcomes of stroke patients. Methods In this pilot randomized controlled trial 32 stroke patients were randomly divided into experimental and control groups from January to June 2017. Patients in both groups received conventional neuro‐rehabilitation five times a week in 3‐h segments for 6 weeks. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…When we conducted the subgroup analysis, the five pooled studies 38,43,50,54,56 revealed a statistically significant effect (WMD, 7.14; 95% CI, 5.36 to 8.93; P < 0.00001; I 2 = 73%). High statistical heterogeneity was still present, and we performed further sensitivity analysis to remove the highly heterogeneous study and assess the stability of this result.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…When we conducted the subgroup analysis, the five pooled studies 38,43,50,54,56 revealed a statistically significant effect (WMD, 7.14; 95% CI, 5.36 to 8.93; P < 0.00001; I 2 = 73%). High statistical heterogeneity was still present, and we performed further sensitivity analysis to remove the highly heterogeneous study and assess the stability of this result.…”
Section: Resultsmentioning
confidence: 98%
“… 44 One study 57 included participants in the acute stroke phase, and 11 studies included participants in the subacute stroke phase. 38 , 43 , 48 – 50 , 52 56 , 59 Seven studies included participants in the chronic stroke phase, 37 , 41 , 42 , 44 47 one study included poststroke participants from the subacute to chronic phase, 51 and three studies did not report or did not clarify the stroke phase. 39 , 40 , 58…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Independence in ADL was measured in two studies using the full FIM (Kulkarni and Sureshkumar, 2018; Nam et al, 2019). Yin et al (2022) used the transfer and locomotion subscales of the FIM as opposed to the scale in its entirety. An original outcome measure was employed in two studies (Liu et al, 2004, 2009).…”
Section: Resultsmentioning
confidence: 99%